2018
DOI: 10.3389/fcimb.2018.00386
|View full text |Cite
|
Sign up to set email alerts
|

H5N1 Influenza a Virus Replicates Productively in Pancreatic Cells and Induces Apoptosis and Pro-Inflammatory Cytokine Response

Abstract: The inflammatory response and apoptosis have been proved to have a crucial role in the pathogenesis of the influenza A virus (IAV). Previous studies indicated that while IAV commonly causes pancreatitis and pancreatic damage in naturally and experimentally infected animals, the molecular mechanisms of the pathogenesis of IAV infection are less reported. In the present study, we showed for the first time that both avian-like (α-2,3-linked) and human-like (α-2,6-linked) sialic acid (SA) receptors were expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 47 publications
0
24
1
2
Order By: Relevance
“…No additional traumatic lesions were noted on examination; all other systems were grossly normal. Laboratory studies revealed elevated random blood glucose of 133 mg/dL, and a complete blood count showed results consistent with known CLL with a total leukocyte count (lymphocyte-predominant) of 50x10 3 /mm 3 (reference range: 4.5-11.0 3 /mm3 ) and elevated levels of atypical lymphocytes. Platelet was 227x10 9 /L, hemoglobin 12.1, and packed cell volume 36.5%.…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…No additional traumatic lesions were noted on examination; all other systems were grossly normal. Laboratory studies revealed elevated random blood glucose of 133 mg/dL, and a complete blood count showed results consistent with known CLL with a total leukocyte count (lymphocyte-predominant) of 50x10 3 /mm 3 (reference range: 4.5-11.0 3 /mm3 ) and elevated levels of atypical lymphocytes. Platelet was 227x10 9 /L, hemoglobin 12.1, and packed cell volume 36.5%.…”
mentioning
confidence: 75%
“…Evidence for influenza causing AP and diabetes comes from in vitro and in vivo studies [3,8]. Influenza viruses replicate only in the presence of trypsin or trypsin-like enzymes, and thus their replication is believed to be restricted to the respiratory and enteric tracts [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a respiratory disease, the liver injury does not typically occur during influenza A virus infection. That respiratory, gastrointestinal, and other mucosal tissues have experienced viral replication or immune damage, but do not influence non-mucosal organs, such as the liver or kidney [11][12][13]. However, some contradicting findings were obtained, such that a pandemic A ⁄ H1N1 (2009) influenza A virus, which is different from seasonal influenza, can lead to liver damage [14].…”
Section: Discussionmentioning
confidence: 99%